The influence of neighbours’ supply network structure on firm’s environmental, social and governance controversies - Qiu, Jilin; Alinaghian, Leila; Brintrup, Alexandra (Taylor & Francis, 2025)
This study investigates how the structural characteristics of a firm's supply network and its neighbouring firms affect their environmental, social, and governance (ESG) controversies. A secondary dataset comprising 18,943 firms and 103,632 contractual links from the global automotive industry was employed to test the hypotheses. Publicly available ESG controversies data for 268 firms were gathered from the Thomson Reuters Eikon database. The results indicated a negative relationship between the interconnectedness of neighbours’ networks and their ESG controversies. The results further revealed a positive association between the centrality of a firm’s neighbours and their ESG controversies. Furthermore, the study highlighted that a firm occupying a bridging position positively moderates the relationship between neighbours’ interconnectedness and ESG controversies. Drawing on a real-world large-scale supply network, our study extends the emerging debate on the criticality of broader supply networks in firms’ sustainability by investigating the role of neighbours’ structural properties in firms’ ESG controversies.
Keywords: 35 Commerce, Management, Tourism and Services; 50 Philosophy and Religious Studies; 5001 Applied Ethics; 3507 Strategy, Management and Organisational Behaviour; Operations Research; ESG controversies; neighbours’ supply network structure; social network analysis; interconnectedness; centrality; bridging